Fetal Skeletal Disorders - Schramm, Thomas; Mommsen, Helge (Ultraschall in der Medizin - European Journal of Ultrasound, 2018)
Skeletal disorders of the fetus are quite common. The incidence is about 5:1000 pregnancies. The disorders affect the extremities or parts of them (dysmelia), the whole skeleton (skeletal dysplasia), the skull (craniosynostosis) and the spine (dysostosis, caudal regression). About half of these diseases are complex. In the majority of cases the complex disorders are caused by single gene mutations or numeric or structural chromosomal aberrations. We explain the classification and diagnostic criteria for prenatal expert and screening ultrasound based on frequent disorders. The main diagnostic challenge concerning malformations of the limbs and craniosynostosis is to find out if they are isolated or symptoms of certain syndromes. In skeletal dysplasia it is clinically important to differentiate lethal entities from non-lethal.Skelettale Erkrankungen des Fetus sind mit 5:1000 Schwangerschaften relativ häufig. Betroffen sein können einzelne Abschnitte der Extremitäten (Dysmelien), das ganze Skelett (Skelettdysplasien), der knöcherne Schädel (Kraniosynostosen) und die Wirbelsäule (Dysostosen, kaudale Regression). In 50 % bestehen komplexe Krankheitsbilder. Für die Mehrzahl der Krankheiten sind genetische Ursachen (Einzelgen-Mutationen, numerische und strukturelle chromosomale Aberrationen) bekannt. Anhand häufiger Krankheitsbilder werden diagnostische Kriterien für die differenzierte Sonografie und das Ultraschall-Screening erläutert.